(untitled) (Critical Journal of Social Sciences, 2026)
This review critically engages with Vivek Chibber’s The Class Matrix: Social Theory after the Cultural Turn (2022), a provocative defence of structural class analysis against culturalist and poststructuralist approaches. The author argues that despite culture’s ubiquity in social life, class structure retains causal primacy in capitalist societies. He proposes that workers' continued participation in capitalism is not grounded in ideological consent but in resignation arising from material constraints. This review systematically unpacks Chibber’s arguments, situates them within historical and theoretical debates, and evaluates the strengths and weaknesses of his intervention. While the book powerfully reinstates materialist critique into contemporary discourse, it also underplays cultural autonomy and intersectionality. The review suggests that Chibber’s framework, though compelling, requires further integration of cultural and identity-based dynamics to capture the complexities of resistance and domination in global capitalism.